ANALISIS PENINGKATAN KOMPETENSI YANG BERBASIS PELATIHAN MODEL RETURN ON TRAINING INVESTMENT (ROTI) (STUDI KASUS DI PT ALPHA AUTOMOTIVE INDONESIA) - Hernasari, Ayati (Jurnal Manajemen dan Bisnis Kreatif, 2018)
Abstrack Increased competence with training required in PT.Alpha Automotive Indonesia has constraints in the form of trouble maker on the performance of employees. One of the efforts made by PT. Alpha Automotive Indonesia to improve employee competence is by training organized by Institutions, Companies and Industrial Estate Management. The objective of the research is to increase competence using training on return on training investment model. The method used is using qualitative research approach. Observational research techniques, interviews, documentation and Focus Group Discussion (FGD). Nature of this research is case study with single case study design (single case study). The result of the research shows that the competence based on employee training in PT. Alpha Automotive Indonesia declared managed to improve the competence of employees of PT. Alpha Automotive Indonesia by showing a good relationship between the training required by the company (training from outside) and training conducted by the company. Keywords: Competence, Training.